1967
DOI: 10.1139/v67-236
|View full text |Cite
|
Sign up to set email alerts
|

Diterpene chemistry. II. The preferential oxidation of the vinyl groups of pimaric and sandaracopimaric acids

Abstract: The use of the Lemieux -von Rudloff technique for the oxidation of the vinyl groups of pimaric (Ib) and sandaracopimaric (IIb) acid methyl esters has been investigated. Although the process leads to the expected C-13 acid V in the case of methyl sandaracopimarate, an unexpected epoxy acid was obtained from methyl pimarate. This product was shown to be the 8p,14p-epoxy-13-a-ketoacid V I I I a , probably arising from an intramolecular process during oxidation of the vinyl group.Canadian Journal of Chemistry. Vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1969
1969
2009
2009

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…10-Bromodecanoic acid was prepared by oxidising the commercially available 11-bromoundec-1-ene with sodium periodate and a catalytic amount of potassium permanganate. 44 The molecular weights of the linear polymers are given in the Experimental section. These linear polymers were cyclodepolymerised using 2 mol% of dibutoxydibutyltin (9) as the catalyst in chlorobenzene at re¯ux temperature for 8 h to give the corresponding cyclic oligomers (3)±( 5) in good yields.…”
Section: Synthesis Of Cyclic Octanoates (3) Decanoates (4) and Dodeca...mentioning
confidence: 99%
“…10-Bromodecanoic acid was prepared by oxidising the commercially available 11-bromoundec-1-ene with sodium periodate and a catalytic amount of potassium permanganate. 44 The molecular weights of the linear polymers are given in the Experimental section. These linear polymers were cyclodepolymerised using 2 mol% of dibutoxydibutyltin (9) as the catalyst in chlorobenzene at re¯ux temperature for 8 h to give the corresponding cyclic oligomers (3)±( 5) in good yields.…”
Section: Synthesis Of Cyclic Octanoates (3) Decanoates (4) and Dodeca...mentioning
confidence: 99%
“…With these two terpenes it is possible that a reactive inethylene group is produced which is oxidized further and may thus lead to a variety of products. Also, one cannot rule out the formation of oxides, as found by Klein and Rojahn (2) in the permanganate oxidation of 1,5-dienes, by Apsimon et al (3) in the oxidation of methyl pimarate, and by us (4) in the oxidation of occidentalol. When the oxidation of menthone was carried out with different amounts of potassium carbonate, similar results (Table 11) as those with cyclohexanone were obtained (see Table I).…”
Section: Resultsmentioning
confidence: 98%
“…In a preliminary experiment it was found that a-terpineol did not give a high yield of the expected product, homoterpenyl methyl ketone. In view of this, and of the different behavior of some dienes as reported recently by Klein and Rojahn (2), Apsimon et al (3), and von Rudloff (4), the oxidation of some cyclic monoterpenes and related cyclo-olefins was studied with the specific purpose of determining whether or not the cyclic mono-olefins, and in particular monoterpenes, would react as predicted with the permanganate-periodate reagent.…”
Section: Introductionmentioning
confidence: 89%
“…Alternatively, permanganate ion would attack the sulfur atom of the thiocarbonyl group or mecaptan 101a, 10lb.The kinetics and mechanisms of the permanganate ion oxidation of thiocarbonyl compounds, thiols, sulfides, sulfoxides, disulfides, sulfinic acids, and sulfenic acids are under investigation TM'; 3 o XIII. PERMANGANATE ION-PERIODATE ION SYSTEM a9,[231][232][233][234][235][236][237][238][239][240][241][242][243] Cleavage of carbon-carbon double bonds takes place smoothly with periodate ion and catalytic amounts of permanganate ion in neutral solution231-243. This general method is useful both preparatively and analytically.…”
mentioning
confidence: 99%